Pengaruh Earning Per Share terhadap Harga Saham pada PT. Bank Mandiri (Persero), Tbk Periode 2010-2019 - Abdul Mannan; Burhan Rifuddin (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of Earning Per Share on Stock Prices at PT. Bank Mandiri (Persero), Tbk Period 2010-2019. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Earning Per Share obtained an average value of 673.83%. The stock price variable obtained an average value of 10.39%. Earning Per Share has a positive and significant effect on stock prices with the regression equation Y = -0.513 + 0.016X, and a correlation coefficient value of 0.690 or has a strong level of relationship with a determination value of 47.6%. Hypothesis testing obtained a significance of 0.027 <0.050.